GAMBARAN PERSEPSI REMAJA TERHADAP POLA KOMUNIKASI ORANGTUA DI KAWASAN KUMUH JATINEGARA - Reneta Kristiani; Lita Patricia Lunanta (Universitas Katolik Indonesia Atma Jaya, 2019)
This research aimed to describe the perception that adolescents had on their parents pattern of communication. This research was held in slum area of Jatinegara in DKI Jakarta. Total of 121 adolescents from 3 districts (Rawa Bunga, Cipinang Besar Selatan, Kampung Melayu) were present in the activities. While we discussed about parenting and communication skills between parents and their offsprings, we explored the perception that the adolescents have about their parents, especially about their communication pattern. This was a descriptive study that wished to explore the communication pattern and relation in family. We used survey method, including questioners for information gathering and implemented observation, interview and small group discussion. To analyze the data, we used descriptive statistical analysis technique and qualitative analysis. We found that in each of the district, the most of the adolescents felt proud of their parents (Rawa Bunga 53%; Kampung Melayu in morning session, 65%; Kampung Melayu in afternoon session, 27%; Cipinang Besar Selatan, 55%). Nevertheless, there were mixed emotion in their hope for their parents. Most of them felt angry to their parents. Some more felt that their parents were not nice enough, felt ashamed, unsignificant, confused and hoped to be understood. These findings suggested that there were still a lot of problems considering how parents communicate and interact with their children, especially their adolescent. Further research needed to be done and actions had to be implemented in order to create a healthy and fully functioning family in the slum area of Jatinegara.